Russian Strategic Interests in Africa - Ksenija Borishpolets (Международная аналитика, 2019)
Status of Africa in Russian foreign policy is characterized by combination of high interests in multidirectional development of cooperation with some restrictions defined by geodistance, political instability, economic specifications of potential partners as well as unpreparedness of Russian business to manage projects within African realities. However development of cooperation between Russia and African states is in trend of Russian international strategy and shall be supported not only by practice of international relations but also by business and humanitarian cooperation and expansion of objective knowledge about African realities. After the period of reduction of Russian presence in Africa in the early 90-th, in recent 10-15 years we witness the inverse trend, that is controversially assessed by Russian and foreign experts. However the author of the article believes that the situation in 2018-2020 is positive, stable and predictable in general. That may be proved by system analysis of the system moments: role of Africa in current world order, cooperation of Russia with African states, promotion of Russian interests in the African region. That is worth mentioning that Russian policy at African direction increases its economic efficiency and material data of Russian-African economic cooperation is gradually growing.